Literature review: Physical education in the covid-19 pandemic - Mujiono Mujiono; Novri Gazali (JUARA : Jurnal Olahraga, 2021)
Currently, teachers and students face problem regarding the learning media used during online learning for physical education. Meanwhile, most students stated that online learning for physical education during this pandemi was not yet fully effective. The purpose of this literature study was to provide a review of the latest research related to physical education learning during the Covid-19 pandemi. The research method is literature study or literature review. Data collection for literature studies was carried out using a database search tool, which is a phase of searching for literature sources from journals starting from 2017 to 2018. This data collection uses the Preferred Reporting Items for Systematic Reviews and Meta Analysis (PRISMA) method. The research was carried out by analyzing journals and then making a summary related to the questions and objectives of the study. The procedure for searching journals to become material in this study is to have criteria that are in accordance with the PICOT procedure. Based on the articles that have been found and analyzed, the online learning model can be applied in physical education with the schoology portal method, and vlogs and can also use the distance learning model with a collaborative approach.